INVESTIGATING OF PRE- SERVICE TEACHERS’ PERCEPTION AND READINESS TO DIGITAL MULTIMODAL LITERACY AT LAKIDENDE UNIVERSITY - Mclean HY Miki (IJLECR (International Journal of Language Education and Cultural Review), 2020)
The era of 21st century learning literacy is not confined to communication based on reading and writing only traditional printed texts. New kinds of literacies extend to multimedia projects and multimodal texts, which include visual, audio, and technological elements to create meanings. Hence, multimodal literacy has gained more attention amongst literacy educators, researchers and curriculum authorities. The purpose of this study is to investigate the perception and the readiness of English teacher in 21st multimodal literacy in this era of new types of communication. The research conducts an online survey research at Lakidende University.  The findings describe the demographic teacher with multimodal literacy which related to the teacher have positive attitude in using a digital media tools, that indicated that they ready to use digital multimodal literacy.The implications of this research give direction and new perspective in using multimodal literacy for English classroom. It suggests that could be better supported by university environment, stakeholders, and government in developing the quality of English teachers’ professional development.